SELF CARE TO FEEL BEST DURING MENSTRUATION (RAJASWALA PARICHARYA): THE IMPACT OF LIFESTYLE MODIFICATION THAT ENHANCE FERTILITY (AYUSHDHARA, 2021)
Out of various Paricharya mentioned in Ayurveda, Rajaswala Paricharya holds an important one. The Charya or code of conduct mentioned for a Rajaswala stree is termed as Rajaswala Parichara. Due to changing lifestyle, physical and mental stress, Mithya Aahar, Woman in reproductive age groups suffer from various conditions related to menstrual cycle like dysmenorrhoea, menorrhagia, irregular menses, PCOS, endometriosis, adenomyosis which increase incidence of infertility also Rajaswala charya is the most neglected part in the society.Acharyas mentioned Aaharas and Charyas which are indicated and contracted for maintaining the health.By the concept of Shuddha Shukra & Shuddha Aartava in the formation of Garbha its very clear that concept of Supraja Jananam i.e., healthy progency begins at the very level of preconceptional care or even before to that in the form of Rajaswala Paricharya.If it followed during menstruation it will get relief from conditions of menstrual abnormalities, infertility and to gain better healthy life of woman.